Kepatuhan Wajib Pajak Di Desa Maluruwu Kecamatan Palue Kabupaten Sikka Ditinjau Dari Aspek Kesadaran Wajib Pajak, Tingkat Penghasilan, Sanksi, Tingkat Pengetahuan Dan Kualitas Pelayanan - Maria Nona Dince; Yoseph Darius Purnama Rangga (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This study aimed to determine the effect of taxpayer awareness, taxpayer income level, taxpayer sanctions, taxpayer knowledge level and service quality on mandatory compliance. The research method used is a quantitative method and a survey approach. The data used in this study is primary data in the form of a questionnaire distributed to taxpayers registered in Maluriwu Village, Palue District, Sikka Regency. The sample used has a sampling limit of 90 respondents. The results showed that the F test results were known to be significant (0.249) greater than 0.05 or above 5%. The results of the T test are known that, a) the significance value of taxpayer awareness is 0.850 > 0.05; b) the significance value of the income level of the taxpayer is 0,-91 > 0.05; c) the significance value of the sanction is 0.164 > 0.05; d) the significance value of taxpayer knowledge is 0.878 > 0.05; e) the significance value of service quality is 0.594 > 0.05. The conclusion, partially or simultaneously, shows that taxpayer awareness, income level, sanctions, knowledge level and service quality do not affect taxpayer compliance. Keywords: Taxpayer Compliance, Taxpayer Awareness, Service Quality, Taxpayer Sanctions, Income Level, Knowledge Level